Precipitation over eastern South America and the South Atlantic Sea surface temperature during neutral ENSO period - Bombardi RJ; Carvalho, Leila M. V.; Jones, C.; Reboita MS (Springer, 2014)
The dominant mode of coupled variability over the South Atlantic Ocean is known as “South Atlantic Dipole” (SAD) and is characterized by a dipole in sea surface temperature (SST) anomalies with centers over the tropical and the extratropical South Atlantic. Previous studies have shown that variations in SST related to SAD modulate large-scale patterns of precipitation over the Atlantic Ocean. Here we show that variations in the South Atlantic SST are associated with changes in daily precipitation over eastern South America. Rain gauge precipitation, satellite derived sea surface temperature and reanalysis data are used to investigate the variability of the subtropical and tropical South Atlantic and impacts on precipitation. SAD phases are assessed by performing Singular value decomposition analysis of sea level pressure and SST anomalies. We show that during neutral El Niño Southern Oscillation events, SAD plays an important role in modulating cyclogenesis and the characteristics of the South Atlantic Convergence Zone. Positive SST anomalies over the extratropical South Atlantic (SAD negative phase) are related to increased cyclogenesis near southeast Brazil as well as the migration of extratropical cyclones further north. As a consequence, these systems organize convection and increase precipitation over eastern South America.